MOVEMENTS, DIVING AND FORAGING BEHAVIOR OF GRAY SEALS (HALICHOERUS-GRYPUS) - THOMPSON, D; HAMMOND, P S; NICHOLAS, K S; FEDAK, M A (1991)
This study presents the first direct observations of the movements and behaviour of free-ranging grey seals at sea. Radio and ultrasonic transmitters were attached to three sub-adult male grey seals which were then tracked from a suitable vessel. Behaviour at sea fell into one of three categories: travelling between haul-outs, short duration trips, and resting adjacent to haul-out sites. Travelling was characterized by direct, relatively fast horizontal movement and by V-shaped dive profiles. During short duration trips the seals swam slower and invariably exhibited square-wave dive profiles, spending approximately 60% of total dive duration at the maximum depth. Resting involved shallow dives close to haul-out sites and an absence of directed lateral movement. The excellent navigational abilities of grey seals are illustrated by the rapid, direct swimming between distant haul-out sites. It is proposed that short duration trips are specifically for foraging because of their association with other piscivores, and because swimming was slow and mostly on or near the sea bed (grey seals are known to feed almost exclusively on demersal and benthic fish). These trips accounted for only 14% of the nine days that seal 1 was tracked. It is also proposed that the habit of diving of the sea bed whilst travelling between distant haul-out sites is to allow opportunistic foraging with only a small increase in total swimming distance.